HORMONE IMBALANCE IN A PATIENT WITH HYPOGONADISM AND CRANIAL BASE TOXOPLASMOSIS - Kostić, Aleksandar; Ilić, Jovan; Ilić, Marija; Golubović, Jagoš; Stojanović, Nikola; Mitić, Milica; Đorđević Spasić, Marina (Acta medicae Medianae, 2026)
Toxoplasmosis is a globally prevalent infection caused by the protozoan parasite Toxoplasma gondii (T. gondii) and represents a widespread and highly adaptable parasitic disease. This case report describes alterations in endocrine function in a patient with T. gondii infection. A 45-year-old man was examined by a neurosurgeon due to visual impairment and intermittent headaches. Magnetic resonance imaging of the brain revealed an extracranial presentation characterized by symmetrical subcentimeter cystic lesions at the skull base. There were no signs of intracranial involvement or abnormalities of the sella turcica. The patient had secondary hypogonadism with decreased levels of both luteinizing hormone and follicle-stimulating hormone. However, T. gondii infection did not result in an increase in testosterone levels. This rare case of a patient with T. gondii infection and hypogonadism highlights the requirement for further research to better understand the pathophysiological mechanisms underlying endocrine alterations associated with this parasite.